2000
DOI: 10.1177/00027640021955504
|View full text |Cite
|
Sign up to set email alerts
|

The Washington Study-Service Year of Eastern Mennonite University

Abstract: The author describes the results of an evaluation of a service-learning program of Eastern Mennonite University. The Washington Study-Service Year, an off-campus program, began in 1976 in Washington, D.C. The author describes briefly the current goals and structure of the program and then describes the evaluation data and results. A variety of methods were used as evaluating tools, including essays of current students, interviews with alumni, and alumni surveys. The short and long-term influence of the program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, participation in service has been found to be associated with entry into service-related occupations. In her retrospective study of the impacts of a service year on college students, Aberle-Grasse (2000) found that former students tended to choose service-related careers over just being active in volunteer community service.…”
Section: Discussionmentioning
confidence: 99%
“…However, participation in service has been found to be associated with entry into service-related occupations. In her retrospective study of the impacts of a service year on college students, Aberle-Grasse (2000) found that former students tended to choose service-related careers over just being active in volunteer community service.…”
Section: Discussionmentioning
confidence: 99%
“…Such outcomes include opportunities for students to gain a deeper understanding about their own social locations and cross borders of power and privilege (Chesler et al 2006; Hattery 2003), to develop a more personal understanding about the connection between social structure and agency (Greenfield 2006), to promote civic engagement and social responsibility (Hironimus-Wendt and Wallace 2009; Kendrick 1996; Wright 2006), and to apply newly acquired research methods skills to “real world” situations (Collier and Morgan 2002; Potter, Caffrey, and Plante 2003). In one study that assessed both the short- and long-term effects of service learning, Aberle-Grasse (2000) found that service learning increased students’ understandings of cross-cultural issues and course concepts, helped students develop communication and interpersonal skills and a strong commitment to service and social change, and led to an increase in students’ self-understanding.…”
Section: Defining Service Learningmentioning
confidence: 99%
“…Recent research provides evidence of the positive benefits, particularly to students, of this aspect of pedagogy in areas of gerontological education (Aberle-Grasse, 2000;Blieszner & Artale, 2001;Brown & Roodin, 2001;Dorfman, Murty, Ingram, Evans & Power, 2004;Hanks & Icenogle, 2001;O'Quin, in press;Rhoads & Howard, 1998;Knapp & Stubblefield, 2000). Cavanaugh (2001) acknowledges, however, that the positive outcomes stem more from personal learning and community service than from content learning.…”
mentioning
confidence: 99%